Uncommon Diseases in Pediatric Age: Commemoration in Cienfuegos of an Essential Event for Cuban Public Health - Jan O´neil González Ramos; Belkis González Aguiar (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
Medicine has developed greatly in the last 50 years. The advances of the last five decades have taken place at the fundamental levels of science and have shown the general outburst of scientific knowledge throughout the world. It is certainly the era of molecular biophysical medicine, an influence that brings together all the traditional disciplines of medicine and unifies them. Therefore, diagnosing uncommon diseases plays an increasingly important role and is performed as early as during pregnancy. In spite of the fact that the access to treatments has become really expensive in developed countries, in Cuba the health system guarantees it for free.